Perancangan Interior Kantor Konsultan Interior dengan Konsep “Grow Creativity” di Surabaya - Axel Hariyanto; Sherly de Yong; Hendy Mulyono (Intra, 2018)
The lack of attention to the comfort and completeness of facilities of the current office design causes the office employees today become less productive and creative, especially in the interior design consultant office in Surabaya. Interior design of Creative Interior Consultant Office with the concept of “Grow Creativity” in Surabaya, is functioned to accommodate all activities undertaken by office employees who are interior designers to make them feel at home while working in the office, to think more creatively, and all activities undertaken in the office can be facilitated well. The design method used is Design Thinking with stages consist of: (1) Discovery (2) Observe (3) Empathize (4) Ideate (5) Decide (6) Prototype (7) Test (8) Implementation. The design concept is based on the comfort of "User" or office user (interior designer) that will be applied in the office design. The benefits that will be perceived by interior designers with the existence of this creative interior consultant office is the availability of an office that can meet all the needs of the interior designers and enable them to work creatively and productively in the office